By forming and solving a suitable quadratic equation, find the solutions of the equation: 3cos(2A)-5cos(A)+2=0

3cos(2A)-5cos(A)+2=0. The first thing we do is use a trignometric identity, namely cos(2A) = 2(cos^2(A))-1. This gives us a new form of the original equation.

3(2(cos^2(A))-1)-5cos(A)+2=0: we expand out the brackets. 6(cos^2(A))-3-5cos(A)+2=0 We collect the like terms and we arrive at the following.

6(cos^2(A))-5cos(A)-1=0: this is a quadratic which is more familiar and by inspection we can simplify. (If we can't use inspection or just want to check, we can always use the quadratic formula).

(cos(A)-1)(6cos(A)+1)=0: we can now see that either cos(A)=1 or cos(A)=-1/6. Hence we know A = 99.6 or 260.4 degrees.

JB
Answered by James B. Further Mathematics tutor

2761 Views

See similar Further Mathematics A Level tutors

Related Further Mathematics A Level answers

All answers ▸

A mass m=1kg, initially at rest and with x=10mm, is connected to a damper with stiffness k=24N/mm and damping constant c=0.2Ns/mm. Given that the differential equation of the system is given by d^2x/dt^2+(dx/dt *c/m)+kx/m=0, find the particular solution.


Prove by induction that n^3+5n is divisible by 3 for every natural number.


Prove by mathematical induction that 11^n-6 is divisible by 5 for all natural numbers n


Expand (1+x)^3. Express (1+i)^3 in the form a+bi. Hence, or otherwise, verify that x = 1+i satisfies the equation: x^3+2*x-4i = 0.


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo

© MyTutorWeb Ltd 2013–2025

Terms & Conditions|Privacy Policy
Cookie Preferences